Tectonic Controls on the Maastrichtian-Danian Transgression in the Magallanes-Austral Foreland Basin (Chile): Implications for the Growth of the Southern Patagonian Andes - Sanchez-Valenzuela, A (Elsevier B.V., 2020)
The Maastrichtian-Danian transgression was one of the most extensive Atlantic-derived marine incursions in Patagonia. This study examines its stratigraphic record and origin in the Magallanes-Austral Basin, revealing an interplay of sedimentation, tectonism, and base-level changes, which contribute to our understanding of foreland basin dynamics. We present a multidisciplinary approach from a relatively poorly documented sector (51°38′-53°50′S) of the basin. This approach includes facies and provenance analysis, palynology, sequence stratigraphy, and U-Pb geochronology. These techniques enable us to evaluate the role of climate, tectonics, and eustasy on the transgression, as well as providing insight into the growth of the Southern Patagonian Andes. A first shallowing-upward cycle (late Campanian to late Maastrichtian) is represented by the transition from outer shelf and upper slope deposits (Fuentes and Tres Pasos formations) to shoreface and deltaic environments (Rocallosa and Dorotea formations), favoured by high erosion rates in the fold-thrust belt and eustatic sea-level drop. A subsequent deepening-upward cycle (late Maastrichtian to Paleocene) records the Atlantic transgression, manifested by estuarine deposits in an incised valley (uppermost Dorotea Formation) and deep-water turbidites (Chorrillo Chico Formation and Cabo Naríz beds). Palynological results suggest a temperate palaeoclimate (~6–17 °C) during the Maastrichtian-Danian, which agrees with significant cooling of the South Atlantic Ocean at this time. Therefore, relative climatic optima are not a driver of marine ingression. The stratigraphic and tectonic evolution of the succession studied suggests that flexural and dynamic subsidence promoted marine incursion into the Magallanes-Austral Basin. Provenance data indicate sediment input to the basin from the Southern Patagonian Batholith, Rocas Verdes Basin remnants, Tobífera Formation, and metamorphic terranes exposed in the hinterland of the Southern Patagonian Andes during the early Maastrichtian. However, by the Paleocene, sediments derived from the hinterland had been structurally dammed during basinward propagation of the fold-thrust belt. © 2020 Elsevier B.V.